High frequency AC power and data distribution system - Lourdes, Steve (Cranfield University, 2011)
At present, power delivery issues are becoming a concern with modern state of the art electrical and electronic systems. The existing power networks, namely the centralized power architecture and the DC distributed power systems are struggling to cope with rigorous demands in some application areas. While active research to improve the current system is being relentlessly pursued, a more radical approach proposing a new power distribution system is increasingly drawing attention. High frequency AC (HFAC) power distribution architecture has been identified as a viable alternative to existing and future systems. The HFAC distributed power system (DPS) was initially proposed in the early 80s for space application and since then it has been considered for many modern ground based applications. This dissertation presents a fresh perspective to the problem by challenging the current notion of viewing the HFAC DPS merely as a passive power distribution system. The possibility of converting the existing system to a more intelligent architecture is investigated. Two fundamental features identified to be crucial for this implementation is the ability to communicate and to control power flow between the various power processing structures in the system. Developing the ♯enabling technologiesα is the primary focus of this research. A data modem designed to enable bidirectional multi node communication over the HFAC bus satisfies part of this requirement. The ability to control power flow is achieved by introducing digital control in the front end HFAC inverter. It is shown that intelligent management of the HFAC DPS offer potential efficiency benefits previously not possible in the traditional implementation. At the subsystem level, the front end inverter, the point of load (POL) converter and the communication module are investigated in depth. Extensive mathematical modelling is undertaken to develop optimal design guides to improve performance of the subsystems. Prototypes are constructed and the models are experimentally validated. In the case of the front end inverter, a multi stage inverter with parallel operation capability incorporating digital control is presented. An integral cycle converter is investigated as part of the POL subsystem and optimal synthesis pattern that improves power factor is identified. The communication subsystem constitutes the HFAC data modem described above. The modem emulates Ethernet style communication and interfaces to a host system via a simple serial communication link. All communication over the HFAC bus is performed transparently to the host. This dissertation contributes to the improvements of HFAC DPS at both the system and subsystem levels. At the system level, implementation of intelligent management of the HFAC DPS is shown to be viable and offers opportunities for improved performance and flexibility not previously possible. At the subsystem level, performance improvement to the individual power processing structures in the system is presented.
© Cranfield University 2011. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner.
Keywords: Power production and energy conversion (non-propulsive); AC power; High frequency AC; Distributed power system